Personal Computing Acceptance Factors in Small Firms: A Structural Equation Model1 - Igbaria, Magid; Zinatelli, Nancy; Cragg, Paul; Cavaye, Angele L.M. (MIS Quarterly, 1997)
This study draws upon the technology acceptance model as the theoretical basis and empirical findings for a pragmatic explanation of key factors affecting personal computing acceptance in small firms. The study uses results from a survey of 358 users in small firms in New Zealand to test a structural model examining the hypothesized relationships among the following constructs: intraorganizational factors, extraorganizational factors, perceived ease of use, perceived usefulness, and personal computing acceptance (i.e., system usage). The findings indicate that perceived ease of use is a dominant factor in explaining perceived usefulness and system usage, and that perceived usefulness has a strong effect on system usage. The results also indicate that exogenous variables influence both perceived ease of use and perceived usefulness, particularly management support and external support. Inconsistent with prior research in large firms, relatively little support was found for the influence of both internal support and Internal training. Implications for the acceptance of personal computing and future research on personal computing acceptance in small firms are discussed.